PLANNING EXCELLENT PROGRAM OF SUSTAINABLE LEARNING THROUGH CLONNING SYSTEM IN ISLAMIC EDUCATIONAL INSTITUTIONS - Rif’an, Ali; Said, Akhmad; Umeirsyah, Umeirsyah (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Quality learning is important and is the responsibility of various parties with sustainable planning stages. This research aims to analyze the roles and functions of stakeholders in designing excellent programs of learning through the cloning system and how the sustainable planning stages in Bahrul Ulum Malang institutions. This research uses descriptive qualitative type. Selection of informants using purposive sampling with snowball sampling technique. Extracting data through participatory observation, guided interviews, document data and FGDs. Data analysis of the interactive model includes data condensation, data display and conclusion drawing / verification. Data validity with triangulation on sources and methods through rival explanation. The results showed that a). The role of the Foundation, Madrasah Head & Deputy, Potential Teachers, experts from LPI Sabilillah through BEST (Be Excellent School Training) activities and madrasah committees have an equally important role because each has a different function in program planning. b). The stages of the sustainable planning process include: Uniting the mindset collectively; Reviewing the Vision, Mission, and goals of the institution; Determining superior programs; Choosing the right teachers and staff; Making strategic learning plans; Providing facilities and utilizing technology; and Encouraging students to excel. This research provides implications about the importance of stakeholder involvement in superior program planning through systematic, measurable and sustainable planning stages so that it is more effective and efficient to achieve the desired learning excellence